Signalling through Class I PI3Ks in mammalian cells. (25th October 2006) - Hawkins, P.T.; Anderson, K.E.; Davidson, K.; Stephens, L.R.
Abstract : It is now accepted that activation of Class I PI3Ks (phosphoinositide 3-kinases) is one of the most important signal transduction pathways used by cell-surface receptors to control intracellular events. The receptors which access this pathway include those that recognize growth factors, hormones, antigens and inflammatory stimuli, and the cellular events known to be regulated include cell growth, survival, proliferation and movement. We have learnt a great deal about the family of Class I PI3K enzymes themselves and the structural adaptations which allow a variety of cell-surface receptors to regulate their activity. Class I PI3Ks synthesize the phospholipid PtdIns(3, 4, 5) P 3 in the membranes in which they are activated, and it is now accepted that PtdIns(3, 4, 5) P 3 and its dephosphorylation product PtdIns(3, 4) P 2 are messenger molecules which regulate the localization and function of multiple effectors by binding to their specific PH (pleckstrin homology) domains. The number of direct PtdIns(3, 4, 5) P 3 /PtdIns(3, 4) P 2 effectors which exist, even within a single cell, creates an extremely complex signalling web downstream of PI3K activation. Some key players are beginning to emerge, however, linking PI3K activity to specific cellular responses. These include small GTPases for the Rho and Arf families which regulate the cytoskeletal and membrane rearrangements required for cell movement, and PKB (protein kinase B), which has important regulatory inputs into the regulation of cell-cycle progression and survival. The importance of the PI3K signalling pathway in regulating the balance of decisions in cell growth, proliferation and survival is clear from the prevalence of oncogenes (e.g. PI3Kα) and tumour suppressors [e.g. the PtdIns(3, 4, 5) P 3 3-phosphatase, PTEN (phosphatase and tensin homologue deleted on chromosome 10)] found in this pathway. The recent availability of transgenic mouse models with engineered defects in Class I PI3K signalling pathways, and the development of PI3K isoform-selective inhibitors by both academic and pharmaceutical research has highlighted the importance of specific isoforms of PI3K in whole-animal physiology and pathology, e.g. PI3Kα in growth and metabolic regulation, PI3Kβ in thrombosis, and PI3Kδ and PI3Kγ in inflammation and asthma. Thus the Class I PI3K signalling pathway is emerging as an exciting new area for the development of novel therapeutics.